Filthy animals [videorecording (DVD)] - North, James T.; North, James T.; Barry, Raymond J., 1939-; Wheeler, Austan; Brown, Ryan Patrick; Santos, Mena Elizabeth; Wessman, Luke (Freestyle Digital Media, 2024)
Lars, a thrill-seeking drug enthusiast, and Freddy, a bodybuilder just out of rehab, seek purpose by hunting child sexual predators. As tensions escalate and their mission derails, Freddy starts to question the true cause for their dangerous crusade. Features an hour of bonus content, including Director's commentary!